Communitary and Individualistic Gods in German and Roman Religion - Zavaroni, Adolfo (Gerión. Revista de Historia Antigua, 2006)
According to two episodes told by Saxo Grammaticus, Othinus was temporarily replaced by Mythothyn and, in a different circumstance, by Ollerus. Analysis shows that the former aspired to personal ownership and glorification, prohibiting votes dedicated to all gods, while the latter shows such an inclination in the name itself (Ullr “Glory”). Analogously Iovis son of Fortuna was the god worshipped by the Roman patricians, while the Ceres- Liber-Libera triad, the early Mercury and Saturn were worshipped by the plebeians as communitary divinities. We may infer that the gods of daily light had been considered promoters of individual power since many centuries.